HALAL INFLUENCERS: A REPRESENTATION OF THE TREND OF HALAL-FOOD CONSUMPTION AMONG THE INDONESIAN MUSLIM MIDDLE CLASS (Jurnal Sosiologi Reflektif, 2022)
Nowadays, the interest of the world's Muslim community in the consumption of halal food has increased. As a country with the largest Muslim population in the world, Indonesia has played important roles in halal-food consumption with attractive trends in the making. In this case, the role of halal influencers on social media is absolute significant in which their presences have shed light on the issue and influenced the trends . This research intends to track the strategy and impact of Muslim influencers in fostering cultural aspects of of halal-food consumption in Indonesia, particularly among Generation Z. This study employed a qualitative approach by using netnography through some influencers’ accounts, such as @aishamaharani, @dianwidayanti, and @anca.id. The findings showed that halal-food influencers could lead generation Z through the trend of halalness into the rules and resources in order to form a new Muslim middle class in encouraging the halal ecosystem in Indonesia.Dewasa ini, minat masyarakat Muslim dunia terhadap konsumsi makanan halal telah meningkat. Indonesia, meskipun merupakan negara dengan jumlah penduduk Muslim terbesar di dunia, konsumsi makanan halal telah berkembang menjadi sebuah trend di kalangan Muslim. Hal ini tidak lepas dari pengaruh halal influencer di sosial media. Penelitian ini bermaksud untuk melacak strategi dan dampak influencer Muslim dalam menumbuhkan budaya konsumsi halal di Indonesia, khususnya di kalangan generasi Z. Penelitian dilakukan dengan menggunakan pendekatan kualitatif melalui netnografi, menelusuri akun-akun halal influencer, seperti @aishamaharani, @dianwidayanti, dan @anca.id. Hasil penelitian menunjukkan bahwa influencer Muslim mampu menggiring generasi Z melalui trend konsumsi halal ke dalam rules dan resource yang mereka harapkan dapat menjadi sarana pembentukan kelas menengah Muslim baru untuk mendorong ekosistem halal di Indonesia.